Penentuan Strategi Penurunan Food Waste dengan Menggunakan Simulasi: Studi Kasus Industri Donut - Juvaldo Hastomo Putra; Ig. Jaka Mulyana; Ivan Gunawan (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2020)
Food waste is a global issue that is currently the center of attention of the world community. From developing countries to developed countries try to develop various methods or approaches to contribute to solving this problem. The existence of food waste in an industry is an indication of an unsustainable system of food production and consumption. This will lead to problems in the form of low total margins on food products and higher operating costs. In this study, experiments were conducted to reduce food waste with a case study at store-level with monte carlo simulation at one of the international franchise bakeries in Surabaya. Analysis of the sale of a franchised bakery. Then, in the form of a template that corresponds to take into account the amount of waste and lost sales (TW / TU) and costs incurred (TLS and TWC). This template is used for simulation with the amount of running equivalent to 3 months. Based on the analysis of the initial simulation results, it is in the form of 3 scenarios that may be applied, namely batch delivery system change, forecasting system changes, and lastly the combination of the two. Based on the results of the scenario, it was obtained that the combined method of forecasting winter-method with delivery policy 2 times a day with the condition of delivery in the form of inventory must be less than 20% of the batch once sent. With this scenario was found the average result per day in the form of waste of 707 products with a total income of Rp91,035,686, waste cost of Rp1,542.22, lost sales of Rp1,248,371.